DANTE ALIGERI'S "DIVINE COMEDY" WORK AND FILMS VISUAL ANALYSIS BASED ON THIS WORK (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article is devoted to the study of the analysis of the works of cinematography, filmed on the basis of Dante's work "Divine Comedy", analyses how the methods used in filmography, the Colorite used, the compositional solution was solved in the interpretation of several films.